A design for switched capacitor and single-switch DC-DC boost converter by a small signal-based PI controller - Ghaderi, Davood; Bulut, Kübra; Tekin, Hakan (Wiley, 2022)
In this study, a switched capacitor (SC)-based single-switch DC-DC boost converter structure operating under the high voltage gain and the low duty ratio is proposed using the PI control technique. High current and voltage stresses across the power switches and power diodes can be reduced by using the projected SC block. In addition, the proposed converter can achieve high voltage gain through shorter duty cycles, which directly reduces the voltage stress and dynamic losses in the power semiconductors. On the other hand, because the proposed converter includes a single power switch under different output powers and different loads, the control process is simpler than multiswitch structures. With the proposed converter, an output voltage of 10 times greater rather than the input voltage is obtained at 0.57 of the duty cycle. In this study, the fundamental functions of the proposed converter and the controller design steps are analyzed mathematically and tested in MATLAB/SIMULINK environment. As a result of the analysis, it was determined that the proposed topology works with a high performance at high frequency and variable load ranges. To validate the proposed converter and theoretical calculations, a 200-W prototype was established under a continuous conduction mode (CCM) working state, with 48-VDC input voltage and 400-VDC output voltage. Finally, the simulation results were tested and verified through the experimental results.
Keywords: continuous (CCM) and discontinuous conduction modes (DCM); DC-DC boost converter; PI controller; switched-capacitor block